Mleko i produkty mleczne w IV-wiecznych traktatach weterynaryjnych - Bartnik, Agnieszka (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2021)
In antiquity, a number of dietary and medicinal properties were attributed to milk, butter and other dairy products. Veterinarians created their own treatments based on the observations and achievements of doctors, but milk was not a popular ingredient in veterinary medicines. Milk from goats, cows and donkeys were used most often